2011
DOI: 10.1186/1755-8794-4-38
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a traditional Chinese Medicine (PHY906) and CPT-11 on the inflammatory process in the tumor microenvironment

Abstract: Background -Traditional Chinese Medicine (TCM) has been used for thousands of years to treat or prevent diseases, including cancer. Good manufacturing practices (GMP) and sophisticated product analysis (PhytomicsQC) to ensure consistency are now available allowing the assessment of its utility. Polychemical Medicines, like TCM, include chemicals with distinct tissue-dependent pharmacodynamic properties that result in tissue-specific bioactivity. Determining the mode of action of these mixtures was previously u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 35 publications
2
58
0
1
Order By: Relevance
“…The results indicated that PHY906 could reduce inflammation when given alone. PHY906 was also able to enhance acute pro-inflammatory processes within the tumor when given in combination with CPT-11 (Wang et al, 2011). …”
Section: Enhancement Of Antitumor Activitiesmentioning
confidence: 92%
“…The results indicated that PHY906 could reduce inflammation when given alone. PHY906 was also able to enhance acute pro-inflammatory processes within the tumor when given in combination with CPT-11 (Wang et al, 2011). …”
Section: Enhancement Of Antitumor Activitiesmentioning
confidence: 92%
“…Using a systemic approach, it applies a "top down" strategy to study the functions and perturbations of a biological system, from the end products of the metabolic network. This endows metabonomics with a holistic view, making it closer to TCM thinking and particularly fit to study pharmacological and toxicological effects of CHM (Lao et al, 2009;Wang et al, 2005Wang et al, , 2011aZhang et al, 2010). Used with a holistic approach, metabonomics has been also exploited to study and characterise Chinese medicine syndromes in several experimental models, recently reviewed (Wang et al, 2011a,b,c;Zhang et al, 2010).…”
Section: Metabolomics and Metabonomicsmentioning
confidence: 97%
“…Preclinical studies suggested PHY906 could enhance the therapeutic indices of a broad spectrum of anticancer agents without changing the pharmacokinetics of the chemotherapeutic agents studied. The mechanisms of action of PHY906 have been studied extensively [88, 89]. Various doses of PHY906 have been tested in phase I and II clinical trials in combination with escalating doses of irinotecan or capecitabine in a variety of solid tumors, and apecitabine for pancreatic and hepatocellular carcinomas.…”
Section: Future Prospective To Improve the Safety Of Traditional Chmentioning
confidence: 99%